Incomplete influenza A virus genomes occur frequently but are readily complemented during localized viral spread - Nathan T. Jacobs (Nature Portfolio, 2019)
The genome of influenza is often incomplete in infected cells, but the implications for infection remain unclear. Here, Jacobs et al. show that an average of 3.6 particles is necessary for productive infection and that coinfection supports efficient complementation within a host but not upon transmission to a new host.